Gen Z Shopping Behavior Factors in Modern Retail Stores, Bojonegoro City, Indonesia - Kustaji; Reza Anggapratama; Nurcholis; Ari Purnomo (Journal of Management Studies and Development, 2025)
This study aims to explore the factors that influence Generation Z’s shopping behavior in modern retail stores in Bojonegoro, Indonesia. As digital technology and social media increasingly shape consumer habits, understanding how Gen Z that characterized by digital nativeness and high connectivity makes purchasing decisions is crucial for retail development. A qualitative approach was employed using in-depth interviews with five purposively selected participants aged 18–25, complemented by field observations and documentation.Thematic analysis revealed four dominant factors influencing Gen Z's retail shopping behavior: technology adoption, social media engagement, influencer impact, and social environment. Respondents indicated that product discovery often starts through platforms like TikTok and Instagram but decisions are finalized after in-store visits, highlighting a hybrid shopping pattern. Influencers, particularly micro-influencers with relatable content, significantly affect trust and intent to buy. Peer opinions and group shopping activities also play a critical role in shaping preferences.These findings suggest that while Gen Z is highly influenced by digital ecosystems, physical retail experiences remain vital. The research contributes to the understanding of hybrid consumer behavior and offers strategic implications for modern retailers seeking to align their marketing and service strategies with Gen Z preferences. Retailers are advised to integrate online and offline experiences, collaborate with digital influencers, and create interactive in-store environments to attract and retain this consumer segment.